Penerapan Model Make a Match Berbantuan Media Flash Finder untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas IV SD - A'yun, Qurroti; Ardianti, Sekar Dwi; Riswari, Lovika Ardana (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the application of the make a match model assisted by flash finder media to improve critical thinking skills in IPAS learning. This study used classroom action research with Kemmis and Mc Taggart spiral model. The subjects in this study were fourth grade students of SD 3 Kalirejo, totaling 24 students consisting of 9 boys and 15 girls. This research took place over two cycles with the stages of planning, implementation, observation, and reflection. The data collection techniques used were observation, interviews, tests, and documentation. While the data analysis techniques used are quantitative and qualitative techniques. The results showed that the application of the make a match model assisted by flash finder media can improve students' critical thinking skills. This is evidenced by the percentage of pre-classical completeness of 33%, increased in cycle I to 58% and increased again in cycle II to 79% with a good category. This research proves that the application of the make a match model assisted by flash finder media can improve students' critical thinking skills in learning IPAS Water Cycle material grade IV SD 3 Kalirejo, so it is necessary to apply the make a match model and develop flash finder media to be applied to other materials in order to improve students' critical thinking skills.